Tindak Tutur Direktif dalam Kumpulan Cerpen Pandawa Kurawa Karya Agus Hiplunudin - Widodo, Mulyanto; Febriyanto, Dedi; Fitriyah, Lailatul (GERAM: Gerakan Aktif Menulis, 2022)
A language is a communication tool used by humans to exchange information between individuals, both in the form of ideas, feelings, and emotions. Every communication process carried out by humans produces speech acts. This study aimed to describe the communication function and strategy for realizing directive speech acts in the collection of short stories Pandawa Kurawa by Agus Hiplunudin. The method used was descriptive qualitative with a pragmatic theory approach. The data source was a collection of Pandawa Kurawa short stories by Agus Hiplunudin. The data was collected through a reading-note technique which was then analyzed descriptively. The research data analysis was carried out by identifying the data, reducing the data, presenting the data, interpreting the data, and concluding the interpretation results. The results showed that the collection of Pandawa Kurawa short stories by Agus Hiplunudin contains a variety of communication functions and strategies for the realization of directive speech acts. The directive speech act was found in communication functions including advising, asking, demanding, ordering, forcing, suggesting, challenging, complaining, encouraging, and asking. Further, the strategies used to realize directive speech acts include a speech strategy without small talk, a speech strategy with positive politeness, and a speech strategy with negative politeness.